Media Management of the Nahdlatul Ulama Da'wah Institute in Promoting Religious Moderation in the City of Padang Sidempuan - Matondang, Ahmad Sultoni; Ritonga, Hasnun Jauhari (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2023)
The focus of this article is on the socialization of religious moderation in the City of Padang Sidimpuan. The city of Padang Sidimpuan has a diverse community, both ethnic, cultural and religious. For peace in the area, it is necessary to cultivate religious moderation in the midst of society which is carried out by the Nahdatul Ulama Da'wah Institute. In this socialization, communication and management are needed because in this process there are a series of concepts that must be prepared in a message before the message is channeled to the communicant. The method used is a qualitative method with data collection techniques using interviews and observation then using descriptive analysis. With the finding that in Padang Sidempuan, the Nahdlatul Ulama Da'wah Institute uses social media as their communication tool in socializing the important role of moderation in people's religious life. The Nahdlatul Ulama Da'wah Institute also thinks about a plan, organization, implementation and supervision that is carried out with the aim of influencing the people of Padang Sidempuan. The Nahdlatul Ulama Da'wah Institute uses social media such as Facebook, Instagram, Whatsapp to disseminate their content which leads to forms of counseling through social media with the aim of stimulating the public for the socialization of religious moderation. Focus kajian artikel ini tentang sosialisasi moderasai beragama di Kota Padang Sidimpuan. Kota Padang Sidimpuan memiliki masyarakat yang beragam, baik etnis, budaya dan agama. Untuk ketentraman di wilayah tersebut, diperlukan penanaman moderasi beragama di tengah masyarakat yang dilakukan oleh Lembaga Dakwah Nahdatul Ulama. Di dalam sosialisasi tersebut diperlukan komunikasi dan manajemen sebab proses tersebut terdapat serangkaian konsep yang harus disiapkan pada suatu pesan sebelum pesan tersebut disalurkan kepada komunikan. Metode yang digunakan adalah metode kualitatif dengan teknik pengumpulan data menggunakan wawancara dan observasi kemudian menggunakan analisis deskriptif. Dengan temuan bahwa di Padang Sidempuan, Lembaga Dakwah Nahdlatul Ulama menggunakan media sosial sebagai alat komunikasi mereka dalam mensosialisasikan peran penting moderasi pada kehidupan beragama masyarakat. Lembaga Dakwah Nahdlatul Ulama juga memikirkan mengenai suatu rencana, pengorganisasian, pelaksanaan dan pengawasan yang dilakukan dengan tujuan untuk mempengaruhi masyarakat di Padang Sidempuan. Lembaga Dakwah Nahdlatul Ulama menggunakan media sosial seperti Facebook, Instagram, Whatsapp untuk menyebarkan konten-konten mereka yang mengarah kepada bentuk penyuluhan melalui sosial media dengan tujuan untuk menstimulus masyarakat atas sosialisasi moderasi beragama.